2022
DOI: 10.1002/hep4.2062
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial dysfunction is an independent predictor of mortality in patients with cirrhosis treated by transjugular intrahepatic portosystemic shunt

Abstract: The present study aimed to investigate (1) the association between left ventricular diastolic dysfunction (LVDD), graded according to the algorithm proposed by the Cirrhotic Cardiomyopathy Consortium, and long‐term survival in patients with cirrhosis undergoing transjugular intrahepatic portosystemic shunt (TIPS) and (2) the additive prognostic value of left atrial (LA) function, as assessed by LA reservoir strain, using two‐dimensional speckle‐tracking echocardiography (2D‐STE). A total of 129 TIPS candidates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…Most CCM studies have been conducted in Europe and North America, where alcoholic cirrhosis predominantly causes the disease, resulting in an unclear prevalence of CCM with diastolic dysfunction in patients with hepatitis B decompensated cirrhosis. Our study revealed a 14.6% incidence of diastolic dysfunction, similar to previous research reporting CCM prevalence rates between 7.4% and 26% [7,11]. In heart diseases, it is commonly observed that left ventricular diastolic dysfunction (LVDD) precedes the onset of left ventricular systolic dysfunction, with a considerable proportion of patients with systolic dysfunction also presenting LVDD [15,16].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Most CCM studies have been conducted in Europe and North America, where alcoholic cirrhosis predominantly causes the disease, resulting in an unclear prevalence of CCM with diastolic dysfunction in patients with hepatitis B decompensated cirrhosis. Our study revealed a 14.6% incidence of diastolic dysfunction, similar to previous research reporting CCM prevalence rates between 7.4% and 26% [7,11]. In heart diseases, it is commonly observed that left ventricular diastolic dysfunction (LVDD) precedes the onset of left ventricular systolic dysfunction, with a considerable proportion of patients with systolic dysfunction also presenting LVDD [15,16].…”
Section: Discussionsupporting
confidence: 88%
“…The Cirrhotic Cardiomyopathy Consortium (CCC) recently proposed a standardized algorithm for quantifying left ventricular diastolic function using multiple echocardiographic parameters in patients with end-stage liver disease [8]. Prior research has indicated that diastolic dysfunction prevalence ranges from 7.4-26% in populations predominantly diagnosed with alcoholic cirrhosis [7,[11][12][13]. However, data regarding patients primarily affected by hepatitis B virus (HBV) infection remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…LV GLS and LAS were measured offline by 2D-STE and using EchoPAC V.203 software (GE-Vingmed Ultrasound), as we previously described 18…”
Section: Methodsmentioning
confidence: 99%
“…The LV endocardial border was manually traced and then automatically tracked by the software through the cardiac cycle. The LV GLS was derived by averaging all segmental strain values and later by averaging values of all apical views 14 18…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation